PENDIDIKAN DEMOKRASI DAN NASIONALISME: Tantangan Menuju Masyarakat Madani di Era Global - ASTUTI DWININGRUM, SITI IRENE (FOUNDASIA, 2005)
Democratic education is an initial step to make a more democratic society majerialize, because the foundation of a civil society is democratic life in social, economic. and political fields. To maintain the nations existence and identity, it is necessary to inculcate learners with nationalism values Plurality principles based on curiul reproduction need to be taught integrated, in the educational process